Serotonin is a gap junction-permeable neuronal tracer in the mouse retina - Szarka, Gergely; Hoffmann, Gyula; Kovács-Öller, Tamás; Völgyi, Béla (Frontiers in Ophthalmology, 2023)
Introduction Gap junctions are dynamically modulated bridges allowing the transcellular passage of ions and small molecules with a molecular mass of up to 1 kDa, a mechanism utilized for molecular communication purposes by living cells. This same mechanism is also exploited by scientists to reveal the existence of gap junction contacts by the cell-to-cell movement of tracers. However, multiple labeling experiments require the availability of multiple gap junction-permeable tracers. Methods To this end, we utilized the well-known transient OFF alpha retinal ganglion cell (RGC)-coupled array as a model system to study and compare the transjunctional movement of neurobiotin (NB), a commonly used tracer, and serotonin, a recently identified tracer. Results Although the transjunctional movement of serotonin has been established in cell cultures, here we show, for the first time, that serotonin is also a potent tracer in in vitro tissue. In addition, serotonin is lighter than the classical gap junction-permeable NB, and thus, we expected that tracer movement would be comparable to or better than that of serotonin. We found that intracellular serotonin injections result in the labeling of the coupled transient OFF alpha RGC array very similar to those of the classical NB-labeled arrays. Both serotonin and NB-injected transient OFF alpha RGCs displayed the well-known pattern with coupled RGCs and a cohort of coupled wide-field amacrine cells (ACs). Discussion By using morphological characteristics, we confirm that the serotonin and the NB-coupled AC arrays are identical, and thereby confirm that serotonin is a potent gap junction-permeable tracer and can be readily used as an alternative to NB in in vitro tissue. Moreover, serotonin can be utilized in parallel with other dyes or tracers, enabling the use of multiple labels in the same material.